2014
DOI: 10.1007/s10884-014-9399-5
|View full text |Cite
|
Sign up to set email alerts
|

Oriented Shadowing Property and $$\Omega $$ Ω -Stability for Vector Fields

Abstract: We call that a vector field has the oriented shadowing property if for any ε > 0 there is d > 0 such that each d-pseudo orbit is ε-oriented shadowed by some real orbit. In this paper, we show that the C 1 -interior of the set of vector fields with the oriented shadowing property is contained in the set of vector fields with the Ω-stability.2010 Mathematics Subject Classification. Primary 37C50.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 31 publications
0
11
0
Order By: Relevance
“…Inequalities (3) imply that if δ is small enough, then dist(φ(t 3 + t, x 0 ), g(T p + t)) < ε/2, t ∈ [−T, 0].…”
Section: Consider the Setsmentioning
confidence: 99%
See 1 more Smart Citation
“…Inequalities (3) imply that if δ is small enough, then dist(φ(t 3 + t, x 0 ), g(T p + t)) < ε/2, t ∈ [−T, 0].…”
Section: Consider the Setsmentioning
confidence: 99%
“…Recently importance of this question appears again, during characterisation of vector fields with the C 1 -robust shadowing properties [3,6,13,14,18]. In particular in a work by the author [13] it was constructed an example of a not structurally stably vector field with the C 1 -robust oriented shadowing property.…”
Section: Introductionmentioning
confidence: 99%
“…To descirbe the dynamics on the underlying manifold, it is usual to use the dynamic properties on the tangent bundle such as hyperbolicity and dominated splitting. A fundamental problem in recent years is to study the influence of a robust dynamic property (i.e., property that holds for a given system and all C 1 -nearby systems) on the behavior of the tangent map on the tangent bundle (e.g., see [4,[6][7][8]10]).…”
Section: Introductionmentioning
confidence: 99%
“…Here we say that thewhere γ Y is the continuation of γ with respect to Y . Very recently, Gan et al [4] showed that the set of all robustly shadowable oriented vector fields is contained in the set of vector fields with Ω-stability. In this direction, the following question is still open: if the chain component C X (γ) of a C 1 -vector field X on a compact boundaryless Riemannian manifold M containing a hyperbolic periodic orbit γ is robustly shadowable, then is it hyperbolic?…”
mentioning
confidence: 99%
“…They showed that a vector field satisfies the Lipschitz periodic shadowing property if and only if the vector field is Ω-stable. It becomes clear that the Lipschitz periodic shadowing property is strictly weaker than the standard shadowing property [4,10,13].…”
mentioning
confidence: 99%